Percepção de pacientes em hemodiálise fora da lista de espera sobre o transplante renal - Pauletto, Macilene Regina (2013)
It is a qualitative search, performed with 15 patients in hemodialysis which have indication to kidney transplant and are off the waiting list, they are patients in a renal clinic in Rio Grande do Sul State, Brazil. The objectives was: describe the perception of patients with indication to renal transplant that are off waiting list about the disease and the dialysis treatment; describe the perception of those patients about the transplant; and, to know the reasons that influence the patients in hemodialysis, with indication to renal transplant, about come not in waiting list. The rules of Resolution 196/96 of Health National Council, Health Department to searches involving human beings were respected. The data collection happened between March and July 2012 through narrative interview of experience. The data was submitted to content thematic analysis. The categories arising of data analysis are to describe and discuss in three articles that compound these study. The first one approaches the perception of patients about the disease and treatment of hemodialysis and resulted in the categories: the discovery of renal disease; changes and limitations of hemodialysis; and, the adaptation to treatment. The analysis of the categories can verify that even though limitation caused by disease and treatment, the patients feel safe and adapted to conditions of life in hemodialysis, and they remain in therapy although with indication to transplant. The second article is about perception of patients about transplant as a treatment that needs cares with possibility of complications, including death. Also, the perceptions about transplant are linked with success histories and the possibility of a new life out of machines. The perception of patients that the transplant is a treatment that demands cares, with possibility of complications, seems to influence in current decision of not come in the list, for implicate in changes and limitations in daily life, for which, the respondents are not prepared. The perception that transplant means a possibility of a new life free of hemodialysis machines, could contribute to consider the therapeutic modality. The third article presents the reasons to do not ingress in the waiting list, which were related with the need of medicines; financial implications and difficulties to ingress in list; uncertainty and negative experiences of transplant; possibilities of complications and return to hemodialysis; and, fear of death. Despite the listed reasons been relevant to do not ingress in waiting list, the need of being informed and clarified about the therapeutics is not discarded. It is important to nursing to know the perception of patients about the disease, treatment and possibility to kidney transplant, as well the reasons that influence to do not choose the renal transplant, with the objective of to orientate educative actions that could to guide, to clarify and respect the choices of patients.